2017
DOI: 10.3390/rel8100210
|View full text |Cite
|
Sign up to set email alerts
|

Association between Health Behaviours and Religion in Austrian High School Pupils—A Cross-Sectional Survey

Abstract: Abstract:The prevalence of risk factors for chronic diseases such as smoking, alcohol abuse, low fruit and vegetable consumption, and lack of physical activity is high among young adults. Health behaviours are influenced by many factors and also by religious orientation, as American studies show. The aim of the present study was to explore whether a similar association with religion exists in Austria (Europe). A cross-sectional survey was carried out in seven randomly selected high schools, whereby a total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The result is confirmed by previous studies, which have found a negative association between religiosity [31] addictive behaviors [6,[8][9][10] and soft drink consumptions [9]. Other studies have found a positive association between spirituality and religious practice and healthy eating behaviors [12,[32][33][34]. However, this research revealed that organized, non-organized and intrinsic religiosity were not associated with healthy eating behaviors.…”
Section: Resultssupporting
confidence: 88%
“…The result is confirmed by previous studies, which have found a negative association between religiosity [31] addictive behaviors [6,[8][9][10] and soft drink consumptions [9]. Other studies have found a positive association between spirituality and religious practice and healthy eating behaviors [12,[32][33][34]. However, this research revealed that organized, non-organized and intrinsic religiosity were not associated with healthy eating behaviors.…”
Section: Resultssupporting
confidence: 88%
“…Generally, religion seems to have a great influence on decisions regarding appropriate health behaviour [ 51 ]. For example, parents who view religion as essential have been found to have a positive attitude towards HPV vaccination for their daughters in a Buddhist society [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our study findings do not contradict what is currently known. For example, higher religiosity is positively associated with healthy behaviors (e.g., diet and exercise) ( Acosta Enriquez et al, 2019 ; Brown et al, 2001 ; Wallace & Forman, 1998 ) and negatively associated with risky behaviors (e.g., smoking and drinking alcohol) ( Gäbler et al, 2017 ; Nagel & Sgoutas-Emch, 2007 ). Most evidence comes from the Western world where Christianity is the most common religion.…”
Section: Discussionmentioning
confidence: 99%